Best practice for evacuation centres accommodating vulnerable populations: A literature review. (June 2020) - Kako, Mayumi; Steenkamp, Malinda; Ryan, Benjamin; Arbon, Paul; Takada, Yosuke
Abstract: Evacuation centres are often the first temporary living spaces for disaster-affected people. These spaces should be safe and provide a minimum standard of living and care for the duration of people's stay. Minimum standards should therefore be regulated and monitored by governments, humanitarian agencies, and other organisations that plan, set-up, and manage evacuation centres. Although such standards have been increasingly understood and implemented in recent times, there has been little peer-reviewed research into the care of vulnerable populations in evacuation centres. This review investigated the processes, practices, and policies for planning, establishing, and managing evacuation centres for vulnerable groups. After the appraisal of retrieved literature, 20 articles were considered as being applicable for analysis. Eleven articles were written in Japanese, one each was published in Australia and the United Kingdom, and seven in the United States. Using thematic analysis, themes emerged relating to planning, setting up, and managing evacuation centres for vulnerable people. The best practices identified included: identifying the needs of vulnerable populations and venue availability in the communities; existence of transparent local government and stakeholder responsibilities; maintaining continuity of care; and community preparedness through training and exercises. To implement these practices, training and exercises are required for all stakeholders involved in operating evacuation centres. Achieving this will provide the platform required to sustainably improve the safety, standard of living and care provided to people in evacuation centres.